Pelatihan Penulisan Comprehension Questions Berbasis High-Order Thinking Skills Bagi Guru Bahasa Inggris SMA/SMK/MA Swasta di Kabupaten Lombok Timur - Lalu Thohir; Amrullah Amrullah; Udin Udin; Lalu Jaswadi Putera (Jurnal Gema Ngabdi, 2020)
Critical thinking is a skill which teachers and students need to have in order to be able to solve their problems appropriately. The teachers should incorporate critical thinking in the teaching and learning activities and one of them is through questioning in the form comprehension questions. This social service program was intended to provide teachers with room for improving their capability in generating comprehension questions which are critical-thinking based. This program was held in SMA Islam Al-Badriyah East Lombok and it was attended by 18 English teachers of Private Senior High Schools located in East Lombok district. The activities within this program included presentation, discussion, working in group, presenting group work task and evaluation. From this social service program, it was found that the English teachers participated in all activities enthusiastically, especially, in the discussion and in generating comprehension questions. The questions generated by the participants were not only in the level of lower-order thinking but also in the level of higher-order thinking. Further, the questionnaire result showed that in general the participants appreciated this program and hoped the similar program to come in the future to improve their competency or professionalism in English language teaching.